Educational, clinical and counselling psychologists' perceptions of and readiness to incorporate brain technologies into their everyday practices. - Hall, Tracey Leigh (My University, 2011)
The aim of this study was to investigate psychologist’s perceptions and willingness to incorporate brain technologies, such as Neurofeedback and qEEG (quantitative electroencephalography), into everyday practice. This research was considered important as numerous studies on the benefits of using these technologies have been documented, yet despite this not many psychologists have incorporated them into their practices. The sample consisted of 50 psychologists in Gauteng who completed a self- administered questionnaire. The data collected was analysed using Thematic content analysis and the emerging themes were examined in line with the research aims. Results from the study indicate that Psychologists’ knowledge and understanding of the brain technologies are limited, more so in the case of qEEG than with Neurotherapy. Resistance towards the incorporation of the technologies is present. The main causes of resistance appear to be related towards a number of concerns or reservations held by psychologists. Amongst these were the need for more research in terms of efficacy and concerns about costs of equipment, training and accreditation. Despite some of the resistance present, psychologists seem to perceive the technologies as useful in treating attention, concentration, learning, anxiety and mood disorders. Psychologists stated that they were generally open to receiving further education and training on these technologies. The study looked at the suggestions and comments made by psychologists concerning what they considered necessary to aid in the incorporation of these technologies.